The intervention effect of mental health knowledge integrated into ideological and political teaching on college students’ employment and entrepreneurship mentality - Zhu, Jiaming; Lei, Lanchuan; Wu, Pengjv; Cheng, Bo; Yang, Xiu-lan; Fu, Jing; Wu, Zhaoxia; He, Fangcheng (Frontiers in Psychology, 2022)
In order to analyze the intervention effect of integrating mental health knowledge into ideological and political teaching on college students’ employment and entrepreneurship mentality, this paper proposes a study to predict the effect of integrated intervention. This research mainly investigates the ideological and psychological conditions of college students from divorced families through questionnaires, compares and analyzes the classification and statistical results of the survey data between groups and within groups, and analyzes the reasons for the ideological and psychological problems of college students. The experimental results show that 30% of college students from divorced families and college students from non-divorced families responded that they do not feel comfortable in places with many people, and the difference between the groups is not significant. Regarding the concept of entrepreneurship, 64.63% of college students from divorced families in urban areas believe that entrepreneurship is a form of learning and should be encouraged. 63.27% of college students from divorced families in rural areas believe that learning should be the first priority and that a business should not be started. 20.41% of college students from divorced families in rural areas and 25.61% of college students from divorced families in urban areas believe that because entrepreneurship provides economic income, it can reduce the burden on families, but the difference is not obvious. In short, this study can provide reference for the ideological and psychological status of college students from divorced families.